2019
DOI: 10.26682/avuod.2019.22.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Implant Different Levels of Zeranol on Growth Performance, Carcass Trait and Body Composition of Awassi Lambs

Abstract: A total of 30 weaned Awassi lambs (3-4 months) with an average body weight of 28.10 ± o.64 kg were divided equally and randomly into 3 groups. The first was left intact, while the 2 nd and 3 rd groups were implanted with zeranol at the rate of 12 and 24 mg, respectively. Each group was kept in a separate pen and fed concentrate (15.067 % C.P. and 2950 kcal/kg) ad lib till they were slaughtered at 40 kg body weight. Results revealed that daily gain, dressing percentage based on body weight and rib eye area aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Similarly, Gecgel et al (2015) and Tufekci and Olfaz (2021) found that about 90% of SFAs are (C16:0, C18:0 and C14) in L. dorsi muscle fat in various genotype of lambs. Alkass et al (2016) noticed that the predominant SFAs types was C16:0, C18:0 and C14:0 in Awassi and Karadi lambs. Such difference could be due to differences in age and body weight at slaughter and quality and quantity of feed consumed (Rajkumar et al,2015) Far as individual fatty acid is concerned, Linolic acid (C18:2) contributed the highest (22.45± 0.31) followed by Oleic (C18:1) (20.29± 0.32) and Palmatic (C16:0) (17.14± 0.28) (Table 2).…”
Section: Resultsmentioning
confidence: 90%
“…Similarly, Gecgel et al (2015) and Tufekci and Olfaz (2021) found that about 90% of SFAs are (C16:0, C18:0 and C14) in L. dorsi muscle fat in various genotype of lambs. Alkass et al (2016) noticed that the predominant SFAs types was C16:0, C18:0 and C14:0 in Awassi and Karadi lambs. Such difference could be due to differences in age and body weight at slaughter and quality and quantity of feed consumed (Rajkumar et al,2015) Far as individual fatty acid is concerned, Linolic acid (C18:2) contributed the highest (22.45± 0.31) followed by Oleic (C18:1) (20.29± 0.32) and Palmatic (C16:0) (17.14± 0.28) (Table 2).…”
Section: Resultsmentioning
confidence: 90%
“…In previous experiments conducted by Alkass and Kak, (4) Alkass and Mahmood (5) and Alkass and Dosky (2) who found that implanting low dosage (12 mg/animal) of zeranol either in lambs or goat kids had no effect on average daily gain, total gain or final weight. These studies also concluded that the lower response of the zeranol may be due to the high ambiance temperature condition (5). (28) who found that the effect of hormone implantation reduced during summer as compared to the winter when they implement lambs with zeranol in Texas USA which has similar weather conditions to Iraq (4, 5).…”
Section: Resultsmentioning
confidence: 99%
“…DEFRA (9) reported that the price of soybean meal, rapeseed meal, maize gluten, brewers' grain, and silage have been increased by approximately 140, 80, 75, 100 and 50% respectively, from 2005 until 2014, and this has encouraged ruminant farmers to maximize feed efficiency in order to reduce animal production cost. Improving feed efficiency is considered as one of the most important factors that increase farmer's income (4). Many feed additives, growth promoters and/or drugs such as herbs, plant secondary compounds and hormones have been used to increase animal feed efficiency, hence, enhancing animal performance and increasing their production (30 and 1).…”
Section: Introductionmentioning
confidence: 99%